2009
DOI: 10.1677/jme-08-0182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a region in the human IRS2 promoter essential for stress induced transcription depending on SP1, NFI binding and ERK activation in HepG2 cells

Abstract: Recent studies have discovered changes in the insulin-/IGF1 signaling affecting glucose metabolism and the molecular pathogenesis of human hepatocellular cancer. Insulin/IGF1 receptor mediates its intracellular effects by recruitment of one out of the four different insulin receptor substrates (IRS). To investigate mechanisms of IRS2 expression, we analyzed transcriptional regulation of IRS2 in human HepG2 cells. We identified a region 688 bp upstream of the translation start codon responsible for w90% of basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The data that we obtained were consistent with the concept that activation of G q/11 signaling in pancreatic β-cells stimulates the PLCβ/PKC pathway (as expected), resulting in the activation of ERK1/2 which in turn stimulates the activity of the Irs2 promoter (also see Udelhoven et al, 2010). Additional studies with IRS2-deficient mice (Withers et al, 1998) demonstrated that the Rq-mediated beneficial effects on β-cell function required the presence of IRS2 (Jain et al, 2013).…”
Section: Expression Of M3r-based Designer Gpcrs In Transgenic Micesupporting
confidence: 90%
“…The data that we obtained were consistent with the concept that activation of G q/11 signaling in pancreatic β-cells stimulates the PLCβ/PKC pathway (as expected), resulting in the activation of ERK1/2 which in turn stimulates the activity of the Irs2 promoter (also see Udelhoven et al, 2010). Additional studies with IRS2-deficient mice (Withers et al, 1998) demonstrated that the Rq-mediated beneficial effects on β-cell function required the presence of IRS2 (Jain et al, 2013).…”
Section: Expression Of M3r-based Designer Gpcrs In Transgenic Micesupporting
confidence: 90%
“…In addition, the translocation induced by TSSC3 overexpression was inhibited by LY294002, a PI3K inhibitor. The association of Sp1 activation or translocation has been shown through the MAPK/ERK pathway (42). However, Sp1 translocation was suppressed by LY294002 in MCF7 cells as shown in a previous study (41) and by the present results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data strongly support the concept that the stimulatory effect on β cell Irs2 expression following activation of a G q -coupled receptor requires stimulation of the PLCβ/PKC pathway, which ultimately leads to enhanced Irs2 promoter activity in an ERK1/2-dependent fashion ( Figure 7A). Interestingly, a recent study (34) demonstrated that ERK activation substantially enhances the activity of the Irs2 promoter by stimulating the binding of the SP1 and NFI transcription factors to a short promoter region.…”
Section: Figurementioning
confidence: 99%